2020
DOI: 10.2478/raon-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed low dose-rate irradiation response in isogenic HNSCC cell lines with different radiosensitivity

Abstract: BackgroundManagement of locoregionally recurrent head and neck squamous cell carcinomas (HNSCC) is challenging due to potential radioresistance. Pulsed low-dose rate (PLDR) irradiation exploits phenomena of increased radiosensitivity, low-dose hyperradiosensitivity (LDHRS), and inverse dose-rate effect. The purpose of this study was to evaluate LDHRS and the effect of PLDR irradiation in isogenic HNSCC cells with different radiosensitivity.Materials and methodsCell survival after different irradiation regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…1a), hyper-radiosensitivity (HRS) is observed in cancer cells exposed to low-dose rate radiotherapy (<0.30 Gy), with a steeper slope of survival curve than that of high-dose rate radiotherapy. When the radiotherapy dose reaches 0.30-0.60 Gy, radiosensitivity begins to shift to increased radioresistance (IRR) (Todorovic et al, 2020). The HRS/IRR phenomenon can be defined using the induced repair model: SF…”
mentioning
confidence: 99%
“…1a), hyper-radiosensitivity (HRS) is observed in cancer cells exposed to low-dose rate radiotherapy (<0.30 Gy), with a steeper slope of survival curve than that of high-dose rate radiotherapy. When the radiotherapy dose reaches 0.30-0.60 Gy, radiosensitivity begins to shift to increased radioresistance (IRR) (Todorovic et al, 2020). The HRS/IRR phenomenon can be defined using the induced repair model: SF…”
mentioning
confidence: 99%
“…HRS is generally detected via fluorescence-activated cell sorting and microscopy [30]. Todorovic et al [10] reported that radioresistant cells were more sensitive to PLDR at a unit dose of 0.3 Gy, wherein radioresistant cells showed more HRS than its parental cells. However, they noted that the enhanced cytotoxic effect of PLDR disappeared at lower unit doses (0.2 Gy), and that HRS could not be observed in radioresistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the feasibility of using LDFRT as a potentiator of chemotherapy has been studied, and the Life 2021, 11, 1295 2 of 15 results of clinical trials have indicated improved efficacy [8]. In addition, the technique of pulsed low-dose rate radiotherapy (PLDR), which involves irradiation with 0.2 Gy at 3 min intervals for a total of 2 Gy, resulting in an apparent dose rate of 0.0667 Gy/min (total 2 Gy irradiation in 30 min), has been used for the purpose of re-irradiation [9,10]. PLDR [11] was developed as an irradiation method that involves applying HRS and reverses dose rate effects.…”
Section: Introductionmentioning
confidence: 99%
“…ECT with BLM was equally effective on naïve and radioresistant tumours, whereas radioresistant tumours were more resistant to ECT with CDDP compared with radionaïve tumours [39]. All these outcomes were associated with increased DNA damage repair in resistant tumour cells [40].…”
Section: Radio- Chemo-and Targeted Drug Resistancementioning
confidence: 96%